Analysis of changes in the genome of the Omsk hemorrhagic fever virus (Flaviviridae: Orthoflavivirus) during laboratory practices for virus preservation - Zhanna S. Tyulko; Artem V. Fadeev; Aleksei G. Vasilenko; Ekaterina A. Gradoboeva; Valerii V. Yakimenko; Andrey B. Komissarov (Вопросы вирусологии)
Introduction. Omsk hemorrhagic fever (OHF) is a severe disease identified in the 1940s in Western Siberia, Russia. Disease is caused by the OHF virus, which belongs to the genus Orthoflavivirus.